Methodological foundations of the conceptual basis of institutional provision of land management and land management at the local level - Kapinos, N. (Land Management, Cadastre and Land Monitoring, 2017)
The theoretical basis of land management at the local level has already been sufficiently worked out, but it can be argued that they have not yet been finally resolved with regard to institutional provision. Therefore, it is expedient to propose an author's vision regarding the essential definition of this concept. In the classical form, this term was used many decades ago and literally meant the "foundation", "the foundation". It has been established that balanced development of land management as a mechanism for the development of the socio-economic, ecological and legal system of land use in the respective territory is ensured by interaction between the whole set of conditions and factors that can be grouped according to qualitative characteristics in six blocks: 1) needs, development goals, developmental tasks ; 2) innovations in the development of land management and land management NTP for land use development; 3) state land policy, land policy of territorial communities; organizational structure of the land management system; 4) normative-legal infrastructure; 5) mentality, culture, public consciousness; 6) economic mechanism, system of social and economic development. Institutional provision of balanced development of land management and land management of territories of territorial communities is possible only if it is possible to achieve the coherence and complementarity of all six blocks and the unidirectionality of their development. Institutional provision of land management and land management at the local level is a set of social interests, elements, actions and institutions aimed at building land relations and land system systems that ensure the harmonious functioning of land use at the local and other hierarchical levels of economic development of the respective territories. Conceptual basis of institutional provision of land management and land management at the local level in the conditions of new land relations and decentralization of power, which includes local land use development programs, land management and urban planning, land formation and land management, and infrastructure provision of land management.Keywords. Land management, land management, institutional provision, land use, territorial community